Developing a Global Perspective in / FOR Science Teacher Education: The Case of Pollination - Reis, Giuliano (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2014)
Science educators at all levels continuously struggle to keep pace with the rapidly developing understanding of the causes and potential solutions to current environmental issues while also trying to enthuse a new generation of passionate and knowledgeable scientists. However, how can future science teachers make science education more attractive ad meaningful to their students? The present paper describes (in a narrative style) an instructional practice that has been performed within a secondary science methods course in a teacher preparation program in Canada. More specifically, it draws on ideas presented in Agenda 21 and the United Nation’s Millennium Development Goals to study the (often neglected) socio-environmental aspects of pollination. Ultimately, the proposed activity aims at promoting the ability of pre-service high school biology teachers to adopt a global education perspective on the science curriculum by (a) recognizing the unintended negative ecological impact caused by humanity’s pursuit of sustainable development and sustainability and (b) reexamining traditional conceptions of scientific and ecological literacies.